A formação docente continuada para datas comemorativas - Linhares, Aline Martins (2018)
The present work, attached to the research line: Historical Knowledge and School Space, of the Professional Master's Degree in History Teaching (ProfHistória), Federal University of Santa Maria, aims, through the formulation of new History teaching methodologies, rethink the approaches, appropriations and uses of Farroupilha ephemeris in School Space. The work presents, as a general objective, to enable the training of teachers for elaboration and presentation of new approaches for the teaching of History of Rio Grande do Sul, based on the understanding and study of Farroupilha ephemeris. It aims to comprehend the meanings and uses of the ephemeris in school space, seeking to understand how teachers understand the approach in relation to the gaucho's image and the celebration of the Farroupilha ephemeris, as well as establishing which mechanisms and methodologies are used by these teachers when working with such themes. The context places of the implementation and investigation of this work were the “State High School Professora Naura Teixeira Pinheiro”, and the “Tancredo Neves State School” (both located in the municipality of Santa Maria). For greater comprehension of reflection and perceptions, the developed practices were organized as follows: Initially contemplating teachers of the three shifts in both schools, and the other activities involved the teachers of the morning shift (State High School Professora Naura Teixeira Pinheiro) and night shift/Youth and Adult education (Tancredo Neves State School). In this way, this work presents, fundamentally, discussions around History teaching, and teachers training, seeking, through the reports of experience of teacher training, to enable the construction of a new approach to think the History of Rio Grande do Sul and especially the Farroupilha ephemeris: Gaucho's Day.